PENGARUH PERBANDINGAN TEPUNG BERAS MERAH PREGELATINISASI DENGAN TERIGU TERHADAP KARAKTERISTIK CRACKERS - Danawati, I Gusti Ayu Atyantha; Jambe, Anak Agung Gede Ngurah Anom; Ekawati, I Gusti Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 1 (2020): Jurnal ITEPA, 2020)
The purpose of this research to find the effect of the comparison of pregelatinization red rice flour with wheat flour on the characteristics of crackers and also to find the best ratio of red rice flour with wheat flour to the characteristics of crackers. This study used a Compeletely Randomized Design (CRD) with a comparison of red rice flour pregelatinization with wheat flour consisting of 6 treatment namely 0% : 100%;10% : 90%; 20% : 80%; 30% : 70%;40% : 60%; 50% : 50%. The treatment repeated 3 times, so that resulting in 18 experimental units. The resulting data is analyzed with variance and if the inter treatment effect on the observed variance, then continue with Duncan test. The result showed that pregelatinization red rice flour and wheat flour significantly affected to water content, protein content, total phenol, and antioxidant activity in crackers and had no significant effect on ash content. The comparison ratio of 50% pregelatinazation red rice flour with 50% wheat flour produces crackers with the best characteristics, namely: water content of 1.15%, ash content of 1.73%, 10.30% protein content, total phenol 158.83% and 45.17% antioxidant activity colour very like, texture crispy, overall liked, aroma,taste and overall acceptance like. Keywords : crackers, red rice , pregelatinized, wheat flour